Watermarking Competency Certificates with Value Images Using the Descrete Cosine Transform (DCT) Method - Anjani, Mutiara Dwi; Fauzi, Achmad; Syahputra, Siswan (Devitara Innovations, 2024)
Image watermarking is a technique for inserting hidden information into digital images to maintain the authenticity and integrity of documents. This study discusses the application of the Discrete Cosine Transform (DCT) method in the watermarking process on the value image stated in the Competency certificate. The DCT method allows the insertion of watermarks on the image's frequency domain, where information can be embedded without compromising the visual quality of the certificate. This implementation aims to ensure that certificates remain authentic and not easily manipulated. The embedding process is carried out by inserting a watermark on a high-frequency component that is invisible to the human eye, while the extraction process is used to verify the authenticity of the certificate. The results show that the DCT method provides reliable protection against image modification, as well as maintains the validity and security of data integrated in the competency certificate digitally.